Efficient routing optimization with discrete penguins search algorithm for MTSP - Mzili, Ilyass; Mzili, Toufik; Riffi , Mohammed Essaid (Decision Making: Applications in Management and Engineering, 2023)
The Travelling Salesman Problem (TSP) is a well-known combinatorial optimization problem that belongs to a class of problems known as NP-hard, which is an exceptional case of traveling salesman problem (TSP), which determines a set of routes enabling multiple salesmen to start at and return to home cities (depots). The penguins search optimization algorithm (PeSOA) is a new metaheuristic optimization algorithm. This paper presents a discrete penguins search optimization algorithm (PeSOA) for solving the multiple traveling salesman problem (MTSP). The PeSOA is evaluated by a set of benchmarks of TSP instances from TSPLIB library. The experimental results show that PeSOA is very efficient in finding the right solutions in a reasonable time.